Přispěje současná penzijní reforma v České republice skutečně k dlouhodobé udržitelnosti důchodového účtu? - Prachař, Ondřej (Univerzita Pardubice, 2013)
The aim of this paper is to identify the current pension reform’s ability to contribute to long-term sustainability of the Czech pension account. Using analytical method the paper describes the so-called small and large pension reforms and discusses their macroeconomic impacts. The paper concludes that the impact of the reforms is ambiguous. The small reform should have a positive effect on the long-term financial sustainability of the pension account mostly due to the number of parametrical changes of the pay-as-you-go pension pillar. On the contrary, the large reform implementing a funded pillar of the social insurance appears to have a negative effect mostly due to an expectable uneven participation of different income groups and its negligible impact on the majority of the population. However, the negative impact caused by the social insurance payments income shortfall should still be viable and it should not amount to a high percentage.
Will the current pension reform in the Czech Republic really contribute to long-term sustainability of the Czech pension account?
Keywords: pension system; pension reform; long-term sustainability; fully-funded pillar; Czech Republic